Deconstructing Theories of Overeducation in Europe: A Wage Decomposition Approach - Seamus McGuinness; Konstantinos Pouliakas (Institute for the Study of Labor (IZA), 2016)
This paper uses data from the Cedefop European Skills and Jobs (ESJ) survey, a new international dataset of adult workers in 28 EU countries, to decompose the wage penalty of overeducated workers. The ESJ survey allows for integration of a rich, previously unavailable, set of factors in the estimation of the effect of overeducation on earnings. Oaxaca decomposition techniques are employed to uncover the extent to which the overeducation wage penalty can be attributed to either (i) human capital attributes, (ii) job characteristics, (iii) information asymmetries, (iv) compensating job attributes or (v) skill needs of jobs. Differences in human capital and job-skill requirements are important factors in explaining the wage premium. It is found that asymmetry of information accounts for a significant part of the overeducation wage penalty for tertiary education graduates, whereas job characteristics and low skill content of jobs explain most of the wage gap for medium-qualified employees. Little evidence is found in favour of equilibrium theories of skills matching and compensating wage differentials. The paper thus highlights the need for customised policy responses (e.g. career guidance; policies to raise job quality) to tackle overeducation.
Keywords: J24; J31; J70; I26; 330; overeducation; skills; mismatch; wages; decomposition